Cellular proliferation in the gills of guppies exposed to Pequi ethanolic extracts - Vieira, Eliane Rosa; Santos, Suzana Costa; Dias Júnior, Walter; Sabóias-Morais, Simone Maria Teixeira (Revista de Biologia Neotropical / Journal of Neotropical Biology, 2015)
The bioactive principles present in the ethanolic extract of “pequi” (Caryocar brasiliensis) have proven to be molluscicidal, fungicidal, trypanocidal, insecticide, and leshimanicidal, taking potentialuse to combat aquatic pests and vectors in public health, and for infectious and invasive diseases in fish.Many plants have proven moluscidida and insecticide effects, and its extracts may contribute to vector control in public health. They also have prophylactic and therapeutic effects in combating diseases infish, for ornamental and aquaculture systems. Most of them are commonly found in tropical and sub-tropical countries. However, to be released in environment or used for health and/or combating invasivediseases in fish, the effect of these products on other representatives of aquatic fauna must be betterunderstood. The guppy (Poecilia vivipara) is generally used as a bioindicator of environmental toxicity, then, he was elected to the experimental studies carried out to verify the action of these extracts. The gills are the target organ, as they come into direct contact with water and because its morphophysi- ological activity in demonstrate the effects of substances present in the water. Therefore, the extracts obtained from the stem and leaf of pequi were analyzed chromatographically, and then the extracts richin flavonoids were selected. The effects in acute tests of these extracts were verified histologically andimmunohistochemically using the molecular marker BrdU (5-bromo-2’-deoxyuridine) that binds to cel-lular DNA during the S phase of their cycle. This work confirms the potential action of “pequi” as inducer of cell proliferation in gills of fish. As the test was conducted in a short period of time and was proventhe occurrence of cell proliferation exist the possibility of having future tumor formation, which indicate a need for studies with long-term exposures.